50 years of the Czech and Slovak Society of Experimental Cardiology - historical background and scientific benefit - Ostadal, B; Novakova, M; Slezak, J (Physiological research, 2024)
The history of the Czech and Slovak experimental cardiology describes a completely unusual curve. The personality of J.E. Purkynje caused this field to reach unprecedented peak at the very beginning of its modern history. The development of experimental cardiology after the death of the great scholar was certainly not linear. Just when it seemed to be raising its head, the German occupation came. Its second hopeful awakening was delayed for a long time by forty years of isolation. The significant limitation of foreign contacts gradually led to the loss of hopefully developing contacts, to professional isolation and lagging behind the stormy development of world science. At the moment of greatest depression, in 1971, in Prague there was created a professional forum that was supposed to enable its intellectual survival and reduce the negative consequences of the "splendid isolation". The Society of Experimental Cardiology (SEC) was founded at the Czechoslovak Physiological Society of the Czechoslovak Medical Society J.E. Purkynje, with the main task of introducing theoretical and clinical cardiologists to the advances in world cardiology. The first meeting was held in 1973 and in 2023 we celebrated already the 50th anniversary of SEC. Moreover, nowadays we see the increasing interest of the young researchers, both experimental and clinical cardiologists, who consider SEC a very attractive platform for their education and professional growth. Key words: Experimental cardiology, Czech and Slovak Society, History, Relationship to clinical cardiology.
Keywords: Slovakia; History, 20th Century; Slovenská republika; kardiologie; Česká republika; Societies, Medical; Biomedical Research; lidé; Cardiology; History, 21st Century; biomedicínský výzkum; společnosti lékařské; Humans; dějiny 21. století; dějiny 20. století; Czech Republic